Case Report: Regaining radioiodine uptake following PRRT in radioiodine-refractory thyroid cancer: A new re-differentiation strategy? - Hadad, Bentolhoda; Askari, Emran; Zakavi, Seyed Rasoul; Aryana, Kamran; Erfani, Soheila; Sahafi, Pegah; Nabavi, Nima; Aghaee, Atena (Frontiers in Nuclear Medicine, 2023)
A 61-year-old woman with a history of metastatic follicular thyroid carcinoma became radioiodine-refractory following two doses of radioiodine (RAI) therapy (cumulative = 230 mCi). While no RAI-avid lesion was noticed in the last post-ablation whole-body radioiodine scan (WBIS), she reported sternal pain, which was accompanied by rapidly rising thyroglobulin levels. 18F-FDG and 68Ga-DOTA-TATE PET/CT was performed, showing metastatic pulmonary nodules and a lytic sternal lesion with acceptable avidity (i.e. uptake ≥ liver). Following four cycles of peptide receptor radionuclide therapy (PRRT) with 177Lu-DOTA-TATE, the thyroglobulin levels dropped significantly, and the sternal pain was partially alleviated. Despite only experiencing grade I thrombocytopenia, the treating physician decided to discontinue PRRT and repeat the diagnostic WBIS. Surprisingly, the scan revealed significantly increased tracer uptake in the sternum. The patient received 200 mCi 131I, and WBIS showed increased RAI uptake in all pulmonary nodules as well as bone metastases. We report a case of RAI-refractory thyroid carcinoma with a somatostatin-receptor expression that re-differentiated and gained significant RAI uptake capacity after PRRT.